HANS BLUMENBERG, UNA CONCEPCIÓN RETÓRICA DE LA POLÍTICA. - Cruz Revueltas, Juan Cristóbal (Andamios)
Despite being one of the pinnacles of philosophy in the second part of the 20th century, the work of Hans Blumenberg is still little known in Mexico and Latin America. In the present work, we will seek to demonstrate that, although Blumenberg is not, in the strict sense, a political philosopher, this does not prevent identifying -from key notions such as distancing, myth, polytheism and rhetoric- a strong political thought coherent with the whole of his work. For the rest, Blumenberg's work constitutes a key and an access route for understanding the intellectual tensions experienced by the culture of the German Federal Republic during the second part of the 20th century.